One-domain approach for studying multiphase transport phenomena in biofilm growing systems. Issue 4 (21st April 2017) - Oliveros-Muñoz, Juan Manuel; Calderón-Alvarado, Martha Patricia; Martínez-González, Gloria María; Navarrete-Bolaños, José Luis; Jiménez-Islas, Hugo
Abstract: The one-domain approach (ODA) was used as an alternative to solve fluid–biofilm interfacial behavior in a 2-D model for diffusion–reaction–convection coupled with prediction of irregular growth of biofilms via a cellular automaton strategy. The simulations exhibited errors of <7% compared with the porosity of a previously reported capillary experimental system. Additionally, biofilm surface geometrical aspects were satisfactorily compared with reports of experimental and similar rigorously simulated benchmark systems. The method developed was applied to simulate typical biofilm systems predicting recirculation flow patterns, interface concentration profiles, and clogging of the inlet section of the capillary tube, which are phenomena that affect the efficiency of diverse biotechnological applications, including membrane bioreactors and biofilters. The ODA method applied to the governing equations of momentum and mass transfer combined with a cellular automaton algorithm is a suitable and straightforward approach for modeling solid-state fermentation at different sophistication levels.